High-quality Finishing Process for Silicon Carbide Optical Components Using Conventional Equipment - Santos,Marcos Valentim Ribeiro dos (2022)
Abstract The development of low-cost high quality surface finishing methods for silicon carbide (SiC) is an arduous task. Nowadays, the SiC mirrors manufacture involves extensive, complex, and costly finishing processes carried out on highly expensive ultra-precise machines. In this work, a cost-effective surface finishing method has been successfully developed, using conventional machines for the optical finishing of SiC. The results showed that the combination of ductile grinding and polishing in conventional low-cost machines allowed to obtain high-quality surface finish on SiC substrates with low roughness (4 - 10 nm Ra ) and optical figure in the range λ / 4 - λ / 8, at a reduced 32 hours total processing time.